[OP.4B.02] NON INVASIVE EVALUATION OF END SYSTOLIC LEFT VENTRICULAR ELASTANCE ACCORDING TO PRESSURE-VOLUME CURVE MODELING DURING EJECTION IN ARTERIAL HYPERTENSION. (September 2016) - Bonnet, B.; Jourdan, F.; Cailar, G du; Fesler, P.
Abstract : Objective: End systolic left ventricular (LV) elastance (Ees) has been previously calculated and validated invasively using LV pressure-volume (P-V) loop. Non invasive studies have been proposed, but clinical application remains complex. The aim of the present study was to 1) estimate Ees according to modeling of LV P-V curve during ejection ("Ejection PV Curve" method) and validate our method with existing published LV P-V loop data; 2) test clinical applicability to detect non invasively a difference in Ees between normotensive and hypertensive subjects. Design and method: Based on P-V curve and a linear relationship between LV elastance and time during ejection, we used a non linear least square method to fit the systolic pressure curve. We then computed slope and intercept of time varying elastance, and calculated Ees as LV elastance at the end of ejection. As a validation, 22 P-V loops obtained from previous invasive studies were digitized and analyzed with our method. To test clinical applicability, P-V curve was obtained from 33 hypertensive and 32 normotensive subjects, using carotid tonometry and real time 3D echocardiography. Results: A good univariate relationship (r 2 = 0.92, p < 0.005) and a good limit of agreement were found between previous invasive calculation of Ees and our new proposed "Ejection P-V Curve" method. In addition, the clinical reproductibility of our method was similar to that of another non invasive method proposed by Chen et al. In hypertensive patients, the increase in arterial elastance (Ea) was compensated by an increase in Ees without change in Ea/Ees (see Figure). Figure. No caption available. Conclusions: Ees can be estimated non invasively from modeling of P-V curve during ejection. This approach was found to be reproducible and sensitive enough to detect an expected difference in LV contractility in hypertensive patients. Due to its non invasive nature, this methodology may have clinical implications in various disease states.